Preparation of Zirconia Catalyst from Zircon Sand and Catalytic Testing for Biodiesel Production - Widayat, Widayat; Almaas Salwa, Diah Ayu; Hasanah, Alfi; Nisa, Khoirun; Saudale, Jeanette Mutiara Paula (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
Heterogeneous catalyst in biodiesel production was developed to overcome the disadvantages of using homogeneous catalyst in the process. Zircon catalysts were known to have amphoteric properties which were suitable for simultaneous esterification-transesterification process in biodiesel production. This study aims to investigate the effect of NaCl impregnated zirconia catalyst for biodiesel production through esterification-transesterification process. Wet impregnation method with varying NaCl weight (10-30% w/w) was used to synthesize the zircon catalyst. The synthesized catalyst was analyzed for its crystallinity and surface morphology using XRD and SEM respectively. The effect of catalyst weight (0.5-2.5% w/w) and operation temperature (50-70oC) to biodiesel product were also investigated. The biodiesel composition, density and viscosity were analyzed using GCMS analysis, picnometry and viscosimetry. The XRD and SEM results showed the synthesized zircon catalyst with 20% w/w NaCl loading had a tetragonal structure. The density, viscosity and free fatty acid content (FFA) of the biodiesel product decreased along with increasing catalyst weight, while the fatty acid methyl ester content (FAME) increased. The increasing FAME content was attributed to increasing active sites which accelerated the esterification-transesterification reaction process, yielding more biodiesel product.